Financial Intermediaries and Economic Development: Evidence on Transaction Costs of Borrowing by the Poor - Swamy, Vighneswara Swamy; Tulasimala, B.K. (Universiti Utara Malaysia, 2011)
This study, while validating the increasing role for financial intermediaries in economic development, analyzes the importance of reducing the transaction costs for financial deepening and, consequently, economic growth.It shows that higher borrowing transaction costs for the poor in particular will retard the long-term growth of rural financial markets.Further, the empirical analysis based on our primary (survey) data indicates that the microfinance models of lending offer considerably lower costs of borrowing than those in regular models of direct lending by banks.The study suggests that microfinance model of lending can provide cost-efficient avenue for speedy financial development and, subsequently, economic growth.